1999
DOI: 10.2337/diabetes.48.10.2039
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance during puberty: results from clamp studies in 357 children.

Abstract: Insulin resistance may be an important cause of a constellation of cardiovascular risk factors in adults, and onset of this syndrome may occur in childhood. However, children normally experience transient insulin resistance at puberty. There were 357 normal children (159 girls, 198 boys) age 10-14 years who underwent euglycemic clamp studies to assess the effects of Tanner stage (T), sex, ethnicity, and BMI on insulin resistance. Insulin resistance increased immediately at the onset of puberty (T2), but return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
616
8
14

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(696 citation statements)
references
References 0 publications
45
616
8
14
Order By: Relevance
“…Gender was included as a fixed factor along with Tanner stage since previous research has shown that girls may have lower SI than boys. 3,22 Subsequently, adjusted 5 Â 2 GLM for log fasting insulin, fasting glucose, log 2-h glucose, log SI, log AIRg, and log DI were run after covarying age, fat mass, and soft lean tissue mass; SI was also included as a covariate when AIRg was entered as the dependent variable. Unadjusted and adjusted models were followed up with pair-wise contrasts using a Bonferroni correction for multiple comparisons.…”
Section: Inpatient Visitmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender was included as a fixed factor along with Tanner stage since previous research has shown that girls may have lower SI than boys. 3,22 Subsequently, adjusted 5 Â 2 GLM for log fasting insulin, fasting glucose, log 2-h glucose, log SI, log AIRg, and log DI were run after covarying age, fat mass, and soft lean tissue mass; SI was also included as a covariate when AIRg was entered as the dependent variable. Unadjusted and adjusted models were followed up with pair-wise contrasts using a Bonferroni correction for multiple comparisons.…”
Section: Inpatient Visitmentioning
confidence: 99%
“…[1][2][3][4] In Caucasian children, decreased SI during puberty is accompanied by increased insulin secretion that normalizes as insulin resistance improves near the end of puberty. 5 Cross-sectionally, Moran et al 3 showed that SI (measured using the euglycemic-hyperinsulinemic clamp) was highest in Tanner stage I, lowest in Tanner stage III (B20% lower than stage I), and near prepubertal levels in Tanner stage V. Using a longitudinal design, Goran and Gower 2 observed that the pubertal transition from Tanner stage I to III was associated with a 32% reduction in SI (measured by the intravenous glucose tolerance test and minimal modeling) in Caucasian and African-Americans which was consistent across a range of body fatness. Our research group has previously demonstrated that Hispanic and African-American children have lower SI in relation to Caucasians, and while Hispanics compensate for their lower SI by increasing insulin secretion, African-Americans exhibit reduced insulin clearance to help maintain normoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…The higher prevalence might in principle be explained by gender differences in anthropometry or physical activity, although such explanations are unnecessary. As noted above, girls are more insulin resistant than boys even after taking anthropometry into account, 15,18,24 and significant differences in physical activity are unable to explain the sex difference in insulin resistance. 24 Diabetes is commoner among male subjects once they enter adulthood, 53 perhaps because they acquire more central fat.…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17][18][19][20][21][22][23] This sex difference in insulin resistance has usually been attributed to differences in adiposity or pubertal stage, but in studies which have adjusted for these factors 15,18 a residual difference remains which has not been explained. We have shown that girls are substantially (B33%) more insulin resistant than boys at 5 years 24 and in the years leading up to puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia and insulin resistance can be detected and managed by testing insulin concentrations [12]. IGF-1, also known as Somatomedin C, is structurally similar to insulin and its production is stimulated by growth hormone (GH).…”
Section: Introductionmentioning
confidence: 99%